Monogenic functions taking values in generalized Clifford algebras - Dinh, Doan Cong (Ukrains’kyi Matematychnyi Zhurnal, 2021)
UDC 512.579Generalized Clifford algebras are constructed by various methods and have some applications in mathematics and physics.In this paper we introduce a new type of generalized Clifford algebra such that all components of a monogenic functionare solutions of an elliptic partial differential equation. One of our aims is to cover more partial differential equations inframework of Clifford analysis. We shall prove some Cauchy integral representation formulae for monogenic functions inthose cases.